Entry Inhibition and Modulation of Pro-Inflammatory Immune Response Against Influenza A Virus by a Recombinant Truncated Surfactant Protein D - Al-Ahdal, Mohammed N.; Murugaiah, Valarmathy; Varghese, Praveen M.; Abozaid, Suhair M.; Saba, Iram; Al-Qahtani, Ahmed Ali; Pathan, Ansar A.; Kouser, Lubna; Nal, Béatrice; Kishore, Uday (Frontiers in Immunology, 2018)
Surfactant protein D (SP-D) is expressed in the mucosal secretion of the lung and contributes to the innate host defense against a variety of pathogens, including influenza A virus (IAV). SP-D can inhibit hemagglutination and infectivity of IAV, in addition to reducing neuraminidase (NA) activity via its carbohydrate recognition domain (CRD) binding to carbohydrate patterns (N-linked mannosylated) on NA and hemagglutinin (HA) of IAV. Here, we demonstrate that a recombinant fragment of human SP-D (rfhSP-D), containing homotrimeric neck and CRD regions, acts as an entry inhibitor of IAV and downregulates M1 expression considerably in A549 cells challenged with IAV of H1N1 and H3N2 subtypes at 2 h treatment. In addition, rfhSP-D downregulated mRNA levels of TNF-α, IFN-α, IFN-β, IL-6, and RANTES, particularly during the initial stage of IAV infection of A549 cell line. rfhSP-D also interfered with IAV infection of Madin Darby canine kidney (MDCK) cells through HA binding. Furthermore, rfhSP-D was found to reduce luciferase reporter activity in MDCK cells transduced with H1+N1 pseudotyped lentiviral particles, where 50% of reduction was observed with 10 µg/ml rfhSP-D, suggestive of a critical role of rfhSP-D as an entry inhibitor against IAV infectivity. Multiplex cytokine array revealed that rfhSP-D treatment of IAV challenged A549 cells led to a dramatic suppression of key pro-inflammatory cytokines and chemokines. In the case of pH1N1, TNF-α, IFN-α, IL-10, IL-12 (p40), VEGF, GM-CSF, and eotaxin were considerably suppressed by rfhSP-D treatment at 24 h. However, these suppressive effects on IL-10, VEGF, eotaxin and IL-12 (p40) were not so evident in the case of H3N2 subtype, with the exception of TNF-α, IFN-α, and GM-CSF. These data seem to suggest that the extent of immunomodulatory effect of SP-D on host cells can vary considerably in a IAV subtype-specific manner. Thus, rfhSP-D treatment can downregulate pro-inflammatory milieu encouraged by IAV that otherwise causes aberrant inflammatory cell recruitment leading to cell death and lung damage.